2023
DOI: 10.2106/jbjs.23.00532
|View full text |Cite
|
Sign up to set email alerts
|

A Pilot Observational Study Evaluating the Diagnostic Capacity of Rotational Thromboelastometry in Periprosthetic Joint Infections

Andreas G. Tsantes,
Dimitrios V. Papadopoulos,
Stavros Goumenos
et al.

Abstract: Background: Periprosthetic joint infections (PJIs) are associated with altered hemostatic dynamics; therefore, coagulation laboratory methods such as rotational thromboelastometry (ROTEM) may be valuable in their diagnosis. The aim of this study was to evaluate the diagnostic role of ROTEM in PJI. Methods: A diagnostic study was conducted including 65 patients who underwent revision total hip arthroplasty or total knee arthroplasty due to PJI (30 patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…The evidence regarding the diagnostic role of viscoelastic studies in PJI is scarce. A recent study by our group evaluated the diagnostic accuracy of ROTEM analysis for PJI in 65 patients who underwent revision total hip and total knee arthroplasty due to PJI or aseptic loosening [25,26]. The findings of this study indicated that development of PJI was associated with higher EXTEM MCF, and that the combined diagnostic accuracy of elevated EXTEM MCF and CRP is improved compared to that of CRP alone.…”
Section: Discussionmentioning
confidence: 98%
“…The evidence regarding the diagnostic role of viscoelastic studies in PJI is scarce. A recent study by our group evaluated the diagnostic accuracy of ROTEM analysis for PJI in 65 patients who underwent revision total hip and total knee arthroplasty due to PJI or aseptic loosening [25,26]. The findings of this study indicated that development of PJI was associated with higher EXTEM MCF, and that the combined diagnostic accuracy of elevated EXTEM MCF and CRP is improved compared to that of CRP alone.…”
Section: Discussionmentioning
confidence: 98%